2021
DOI: 10.1097/jxx.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioner and physician assistant onboarding in a family medicine practice

Abstract: The nurse practitioner (NP) and physician assistant (PA) professions are rapidly growing. Historically, these professions have filled a health care delivery gap caused by lack of health care access and physician shortages. Many medical practices are more accustomed to adding new physicians as compared with adding new NPs or PAs. This article describes one institution's approach to develop and implement a successful NP/PA onboarding program.Several key components are discussed, including (1) established roles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…A successful onboarding program also has the potential to help new hires find meaning in their work, improve role clarity, self-efficacy, and perceived fit (Bauer, 2021). Within health care organizations, several researchers have found initial positive outcomes from implementation of their onboarding programs (Chaney et al, 2021; Erickson et al, 2021). Pittman et al (2021) interviewed CHC leaders and found higher productivity among PAs and NPs in CHCs that offered dedicated time for onboarding and structured education programs.…”
Section: Introductionmentioning
confidence: 99%
“…A successful onboarding program also has the potential to help new hires find meaning in their work, improve role clarity, self-efficacy, and perceived fit (Bauer, 2021). Within health care organizations, several researchers have found initial positive outcomes from implementation of their onboarding programs (Chaney et al, 2021; Erickson et al, 2021). Pittman et al (2021) interviewed CHC leaders and found higher productivity among PAs and NPs in CHCs that offered dedicated time for onboarding and structured education programs.…”
Section: Introductionmentioning
confidence: 99%
“…As noted in our studies and the literature, effective mentoring is critical. 13,[23][24][25] Self-confi dence and autonomy are two consistent factors that assist in role transition and job satisfaction. 24,25 Faraz found that "intrinsic" factors such as self-doubt, stress regarding the role, and feelings of isolation need addressing during the transition along with "extrinsic" factors such as suffi cient time to discuss challenging patients and ethical dilemmas.…”
Section: ■ Discussionmentioning
confidence: 99%
“…12 The new NP graduate is more likely to participate in an onboarding program developed by a clinical practice or network. 1,2,[13][14][15][16][17] ■ Purpose This article explores the experiences of the new NP's onboarding process. It presents data from two qualitative studies.…”
mentioning
confidence: 99%
“…A successful onboarding program also has the potential to help new hires find meaning in their work and improve role clarity, self-efficacy, and perceived fit 14. Several researchers have found initial positive outcomes from healthcare organizations' implementation of onboarding programs 15,16. Pittman and colleagues interviewed CHC leaders and found higher productivity among PAs and NPs in CHCs that offered dedicated time for onboarding and structured education programs 17.…”
mentioning
confidence: 99%
“…14 Several researchers have found initial positive outcomes from healthcare organizations' implementation of onboarding programs. 15,16 Pittman and colleagues interviewed CHC leaders and found higher productivity among PAs and NPs in CHCs that offered dedicated time for onboarding and structured education programs. 17 Also, Erickson and colleagues published a description of a primary care onboarding program that demonstrated positive outcomes among PAs and NPs, including increased engagement, reduced turnover, and higher clinical productivity.…”
mentioning
confidence: 99%